POLICING AS ADMINISTRATION - Slobogin, Christopher (University of Pennsylvania law review, 2016)
Police agencies should be governed by the same administrative principles that govern other agencies. This simple precept would have significant implications for regulation of police work, in particular the type of suspicionless, group searches and seizures that have been the subject of the Supreme Court's special needs jurisprudence (practices that this Article calls "panvasive"). Under administrative law principles, when police agencies create statute-like policies that are aimed at largely innocent categories of actors—as they do when administering roadblocks, inspection regimes, drug testing programs, DNA sampling programs, and data collection—they should have to engage in notice-and-comment rulemaking or a similar democratically oriented process and avoid arbitrary and capricious rules. Courts would have the authority to ensure that policies governing panvasive actions are authorized by statute and implemented evenhandedly, both in individual instances and as they are distributed within the agency's jurisdiction. Furthermore, these principles would apply regardless of whether the panvasive practice has been designated a search or seizure under the Fourth Amendment.